THE EFFECTIVENESS OF PROBLEM-BASED LEARNING MODELS ON SOCIAL STUDIES LEARNING OUTCOMES AT SDN 234 INPRES TAKALAR DISTRICT - Syamsuriyanti; Nur Ismayati (SOLIDARITY: Journal of Social Studies, 2022)
The formulation of the problem in this study is whether the Problem Based Learning Model is effective on the learning outcomes of Social Science students in Class V SD Negeri 234 Inpres Takalar City, Takalar Regency. This study aims to determine the effectiveness of the Problem Based Learning learning model on learning outcomes in Social Science Class V SD Negeri 234 Inpres Takalar City, Takalar Regency. This type of research is a pre-experimental research in the form of one group pretest posttest, which is an experiment. The experimental unit of this research was the fifth grade students of SD Negeri 234 Inpres Takalar Kota. The results of the descriptive statistical analysis on the learning outcomes of Social Sciences with the Problem Based Learning Learning Model show better results than before using the Problem Based Learning Learning Model. The results of inferential statistical analysis using the t-test formula, it is known that the tcount obtained is 12.75 with a frequency of dk = 24-1 = 23. At the 5% significance level, the ttable value = 1.71. So, tcount > ttable or 12.75 > 1.71. This proves that the application of Problem Based Learning learning model in Social Science learning has an influence so that it can be said to be effective than before the use of Problem Based Learning Learning Model. Keywords: the effectiveness of problem based learning model, social science learning outcomes.